Estrogenic Regulation of the GnRH Neuron - Radovick, Sally (Frontiers in Endocrinology, 2012)
Reproductive function is regulated by the secretion of luteinizing hormone (LH) and follicle-stimulating hormone (FSH) from the pituitary and the steroid hormones from the gonads. The dynamic changes in the levels of the reproductive hormones regulate secondary sex characteristics, gametogenesis, cellular function and behavior. Hypothalamic GnRH neurons, with cell bodies located in the basal hypothalamus, represent the final common pathway for neuronally derived signals to the pituitary. As such, they serve as integrators of a dizzying array of signals including sensory inputs mediating information about circadian, seasonal, behavioral, pheromonal and emotional cues. Additionally, information about peripheral physiological function may also be included in the integrative signal to the GnRH neuron. These signals may communicate information about metabolic status, disease or infection. Gonadal steroid hormones arguably exert the most important effects on GnRH neuronal function. In both males and females, the gonadal steroid hormones exert negative feedback regulation on axis activity at both the level of the pituitary and the hypothalamus. These negative feedback loops regulate homeostasis of steroid hormone levels. In females, a cyclic reversal of estrogen feedback produces a positive feedback loop at both the hypothalamic and pituitary levels. Central positive feedback results in a dramatic increase in GnRH secretion (Sisk and others 2001; Clarke 1993; Moenter, Brand and Karsch 1992; Xia and others 1992). This is coupled with an increase in pituitary sensitivity to GnRH (Turzillo, DiGregorio and Nett 1995; Savoy-Moore and others 1980), which produces the massive surge in secretion of LH that triggers ovulation.